MIGRATION DYNAMICS: A SCIENTIFIC EXPLORATION OF MODERN TRENDS IN INTERNATIONAL LABOR MOBILITY - Baxtiyor Zabixullayevich Fayzullayev; Dr. Summera Khalid (PT. Antis International Publisher, 2024)
General Background: International labor mobility is increasingly pivotal in shaping global economies and societies. Specific Background: Recent trends highlight the intricate factors influencing migration, driven by globalization and demographic changes. Knowledge Gap: Despite extensive studies, a comprehensive understanding of the interrelated economic, social, and policy dimensions remains limited. Aims: This study aims to explore these interconnected factors and their implications for contemporary labor migration. Results: The findings reveal a complex interplay where technological advancements and demographic shifts significantly affect workforce movement, while economic imperatives and social dynamics further complicate these trends. Novelty: By employing a mixed-methods approach that integrates quantitative analyses, case studies, and policy reviews, this research offers fresh insights into the multifaceted nature of international labor migration. Implications: The study underscores the importance of a holistic framework for policymakers to navigate the challenges and opportunities of labor mobility, ensuring strategies that effectively harness its benefits while addressing its complexities.